Management of prematurely erupted teeth in newborns - Rahul, Morankar (BMJ Case Rep, 2018)
The majority of natal and neonatal teeth are prematurely erupted primary teeth, whereas few are supernumerary in origin. They most commonly occur in mandibular central incisor region and often can lead to difficulty to the mother during breast feeding and tongue ulceration in newborn. Moreover, since majority of these have poorly developed roots and are mobile, there is always a fear of aspiration into respiratory passage. Extraction therefore is the most commonly rendered treatment for these teeth. This paper comprises cases of natal and neonatal teeth describing about their clinical characteristics and sequel. This paper has also highlighted the factor which needs to be considered during the management of natal/neonatal teeth and protocol followed at our centre.